2020
DOI: 10.1007/s00204-020-02695-5
|View full text |Cite
|
Sign up to set email alerts
|

Cellular levels and molecular dynamics simulations of estragole DNA adducts point at inefficient repair resulting from limited distortion of the double-stranded DNA helix

Abstract: Estragole, naturally occurring in a variety of herbs and spices, can form DNA adducts after bioactivation. Estragole DNA adduct formation and repair was studied in in vitro liver cell models, and a molecular dynamics simulation was used to investigate the conformation dependent (in)efficiency of N 2 -(trans-isoestragol-3′-yl)-2′-deoxyguanosine (E-3′-N 2 -dG) DNA adduct repair. HepG2, HepaRG cells, primary rat hepatocytes and CHO cells (including CHO wild-type and three NER-deficient mutants) were exposed to 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…In 1984, Phillips et al found that DNA adducts detected upon estragole, methyleugenol, and safrole exposure of B6C3F1 mice were still present 22 days after the final treatment. We recently corroborated the persistence of the major estragole DNA adduct (E-3′- N 2 -dG) with over 80% of the adduct level remaining in rat hepatocytes and human HepaRG cells after 72 h of repair …”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…In 1984, Phillips et al found that DNA adducts detected upon estragole, methyleugenol, and safrole exposure of B6C3F1 mice were still present 22 days after the final treatment. We recently corroborated the persistence of the major estragole DNA adduct (E-3′- N 2 -dG) with over 80% of the adduct level remaining in rat hepatocytes and human HepaRG cells after 72 h of repair …”
Section: Discussionmentioning
confidence: 64%
“…In line with this observation, we previously demonstrated that, when HepaRG cells and primary rat hepatocytes were exposed to the related alkenylbenzene estragole for 2 h, they appeared to contain still more than 70% of the formed DNA adducts upon a subsequent 72 h recovery period in the absence of the alkenylbenzene. This pointed at limited repair and resistance toward NER mediated DNA adduct elimination . Resistance toward NER mediated DNA adduct repair has also been reported for DNA adducts of some other genotoxic carcinogens including AFB1 FAPY adduct derived from aflatoxin, ALII- N 6 -dA adduct derived from aristolochic acids, and the polycyclic aromatic hydrocarbon (PAH) diol epoxide- N 6 -adenine DNA adduct formed upon exposure to fjord-type PAHs …”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations